Studi Literatur: Peran Caregiver Untuk Peningkatan Perawatan Kesehatan Pada Pasien Demensia - Riskha Dora Candra Dewi; Kushariyadi (ARTERI : Jurnal Ilmu Kesehatan, 2020)
The role of caregivers for dementia patients to improve health care is not yet optimal. Dementia patient care is an experience-based effort for complex dementia patients that can increase the psychological pressure of caregivers. The aim of the study was to determine the effectiveness of the caregiver's role in dementia patients to improve health care. Search strategies for English-language studies that are relevant to the topic are carried out using the ScienceDirect, SagePub, Springer databases limited from 2014 to 2020. The keywords used are "caregiver", "dementia", "health care", "role". Fulltext articles are reviewed to select studies that fit the criteria. The inclusion criteria in this review are health workers, caregivers. A search using the keywords above with the ScienceDirect, SagePub, Springer database that met the inclusion criteria was only 22 articles. Research examined in this article uses a variety of methods, namely systematic literature review by 1 articles, RCT by 4 articles, interview by 1 articles, qualitative study by 5 articles, quasi-experimental study 2 article, participatory research of 1 article, bootstrapping methods of 1 article, scoping review of published literature by 1 articles, quantitative study by 1 articles, cohort study path analysis by 1, a survey to clarify the evaluation by 1, SEM by 1, standardized protocol by 1. Research using random techniques as much as 10 articles, while those using non-random techniques as many as 12 articles. The role of caregivers for dementia patients to improve health care is an effective experience-based effort and is the most appropriate activity for elderly patients with dementia. Enhance the role of the caregiver by changing the caregiver's perception of a more positive view of his role.